Experts' considerations on HLA‐haploidentical stem cell transplantation. (26th April 2014) - Patriarca, Francesca; Luznik, Leo; Medeot, Marta; Zecca, Marco; Bacigalupo, Andrea; Di Bartolomeo, Paolo; Arcese, William; Corradini, Paolo; Ciceri, Fabio; Vago, Luca; Kanakry, Christopher G.; Fleischhauer, Katharina; et al.
Abstract Recently, novel strategies to control graft‐versus‐host disease and facilitate engraftment have allowed an increasing number of human leukocyte antigen (HLA)‐haploidentical hematopoietic stem cell transplantation (haploHSCT) to be performed. A meeting was convened to review the biological rationale and the clinical results of various T‐cell‐depleted (TCD) and T‐cell‐replete (TCR) HLA‐haploidentical 'transplant platforms'. The objective of the meeting was to promote discussion and consent among leading researchers in the field on three main crucial issues for haploHSCT: (i) eligibility criteria, (ii) choice of the most suitable donor, and (iii) choice of the most appropriate transplant platform. The experts in attendance agreed that a patient who is eligible for an allogeneic transplant and lacks an HLA‐identical sibling or an HLA‐matched unrelated donor should be considered for an alternative donor transplant. Together with the experience of the individual center, the most important decision criteria in choosing an alternative donor source should be the rapidity of transplantation so as to avoid disease relapse/progression. The choice of the mismatched donor should be driven by younger age, ABO blood group compatibility, and Cytomegalovirus status. If a TCD transplant is planned, NK‐alloreactive donors and/or the mother should be preferred. Prospective comparative studies are needed to establish the relative efficacy of different transplant platforms. However, expertise in stem cell manipulation and in adoptive immunotherapy is essential if a TCD transplant platform is chosen.